2014
DOI: 10.2478/pjph-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

The role of Th17 lymphocytes in pathogenesis of autoimmune arthritides

Abstract: Th17 cells are newly described population of lymphoctyes, that recruits neutrophils to the site of inflammation and activate inflammatory phenotype of various tissues. They also play a pivotal role in autoimmune diseases and cancers. These cells secrete mainly different isoforms of IL-17, but also IL-21 and IL-22. Rheumatoid arthritis and juvenile idiopathic arthritis are the most common autoimmune joints’ inflammatory disease, affecting respectively adults and children. For a long time the immunopathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In the study with limited number of NSC-LC patients, Pogoda et al demonstrated that CD14 + HLA-DR -/low MDSCs is not the only population that take part in tumor induced immunosuppression (27). Beyond MDSC they showed that CD14 + HLA-DR + monocyte population secreted significant amounts of IL-10 in lymph node samples, and IL-1β and TNF in peripheral blood, lymph nodes and tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the study with limited number of NSC-LC patients, Pogoda et al demonstrated that CD14 + HLA-DR -/low MDSCs is not the only population that take part in tumor induced immunosuppression (27). Beyond MDSC they showed that CD14 + HLA-DR + monocyte population secreted significant amounts of IL-10 in lymph node samples, and IL-1β and TNF in peripheral blood, lymph nodes and tumor tissue.…”
Section: Discussionmentioning
confidence: 99%